17β‐estradiol upregulates GREB1 and accelerates ovarian tumor progression in vivo. Issue 5 (25th February 2014) - Laviolette, Laura A.; Hodgkinson, Kendra M.; Minhas, Neha; Perez‐Iratxeta, Carol; Vanderhyden, Barbara C.
<x xml:space="preserve">Abstract</x> Exogenous 17β‐estradiol (E2) accelerates the progression of ovarian cancer in the transgenic tgCAG‐LS‐TAg mouse model of the disease. We hypothesized that E2 has direct effects on ovarian cancer cells and this study was designed to determine the molecular mechanisms by which E2 accelerates ovarian tumor progression. Mouse ovarian cancer ascites (MAS) cell lines were derived from tgCAG‐LS‐TAg mice. Following intraperitoneal engraftment of two MAS cell lines, MASC1 and MASE2, into SCID mice, exogenous E2 significantly decreased the survival time and increased the tumor burden. Microarray analysis performed on MASE2‐derived tumors treated with E2 or placebo showed that E2 treatment caused the upregulation of 197 genes and the downregulation of 55 genes. The expression of gene regulated by estrogen in breast cancer 1 (Greb1) was upregulated in mouse tumors treated with E2 and was overexpressed in human ovarian cancers relative to human ovarian surface epithelium, suggesting a role for GREB1 in human ovarian tumor progression. RNA interference‐mediated knockdown of GREB1 in MASE2 cells decreased their proliferation rate in vitro and increased survival time in mice engrafted with the cells. These results emphasize the importance of E2 in ovarian tumor progression and identify Greb1 as a novel gene target for therapeutic intervention.